2021
DOI: 10.1021/acs.jpcb.1c05256
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Fields as a Tool to Analyze Enzyme Reaction Mechanism Variants and Reaction Steps

Abstract: Catalytic fields representing the topology of the optimal molecular environment charge distribution that reduces the activation barrier have been used to examine alternative reaction variants and to determine the role of conserved catalytic residues for two consecutive reactions catalyzed by the same enzyme. Until now, most experimental and conventional top-down theoretical studies employing QM/MM or ONIOM methods have focused on the role of enzyme electric fields acting on broken bonds of reactants. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In addition to its active site, an enzyme includes a protein scaffold that consists of the majority of enzyme residues. The protein scaffold not only plays key roles in the substrate/cofactor binding and substance transportation but also is vital to the boost of catalytic efficiency of the enzyme via the electrostatic stabilization effect. Especially, the scaffold residues are shown to contribute to the preorganized electric field in the active site of natural enzymes, which can stabilize the charge distribution of the transition state (TS) more than that of the reactant state (RS), leading to acceleration of the catalytic rate. , In contrast to natural enzymes that can optimize their protein scaffold through billions of years of evolution, the design of de novo enzymes mainly focuses on the active site, while the scaffolds of the de novo enzymes may lack sufficient electrostatic preorganization as in natural enzymes, which limits the catalytic efficiency of the de novo enzymes. , Accordingly, systematic evaluation of the TS stabilization (or destabilization) effects of the electric fields generated by the scaffold residues is key to both understanding the emergence of the eminent catalytic activity of natural enzymes and the rational design of de novo enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its active site, an enzyme includes a protein scaffold that consists of the majority of enzyme residues. The protein scaffold not only plays key roles in the substrate/cofactor binding and substance transportation but also is vital to the boost of catalytic efficiency of the enzyme via the electrostatic stabilization effect. Especially, the scaffold residues are shown to contribute to the preorganized electric field in the active site of natural enzymes, which can stabilize the charge distribution of the transition state (TS) more than that of the reactant state (RS), leading to acceleration of the catalytic rate. , In contrast to natural enzymes that can optimize their protein scaffold through billions of years of evolution, the design of de novo enzymes mainly focuses on the active site, while the scaffolds of the de novo enzymes may lack sufficient electrostatic preorganization as in natural enzymes, which limits the catalytic efficiency of the de novo enzymes. , Accordingly, systematic evaluation of the TS stabilization (or destabilization) effects of the electric fields generated by the scaffold residues is key to both understanding the emergence of the eminent catalytic activity of natural enzymes and the rational design of de novo enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that during the first step of the aminoacylation reaction, the aminoacyl adenylate is formed from adenosine triphosphate (ATP) and the substrate amino acid with the release of inorganic pyrophosphate through a trigonal bipyramidal transition state. , In the subsequent charging step, the amino acid moiety is transferred from the aminoacyl adenylate to the A76 nucleotide at the 3′-terminal end of the tRNA. The amino acid is attached to the hydroxyl group of the adenosine via the carboxyl group, which requires deprotonation of the 2′-OH or 3′-OH group of tRNA. The deprotonated 2′- or 3′-OH group then attacks the carbonyl carbon of the aminoacyl adenylate leading to the transfer of the aminoacyl group to the 2′- or 3′-O atom of A76 and release of adenylate monophosphate (AMP).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and computational studies have been performed to understand the mechanism of the aminoacylation reaction. The crystallographic study of class I GlnRS proposed that a nonbridging phosphate oxygen of glutaminyl adenylate acts as the base that deprotonates the 2′-OH of tRNA due to their proximity .…”
Section: Introductionmentioning
confidence: 99%
“…Yang and co-workers construct an integrated structure–kinetics database, IntEnzyDB, which they use to predict rate-perturbing single amino acid mutations in hydrolases based on statistical profiling of these enzymes . Finally, Sokalski and co-workers illustrate the power of catalytic fields to analyze enzyme reaction mechanisms and predict new variants at low computational cost, using histidyl tRNA synthases as a model system …”
mentioning
confidence: 99%
“…25 Finally, Sokalski and co-workers illustrate the power of catalytic fields to analyze enzyme reaction mechanisms and predict new variants at low computational cost, using histidyl tRNA synthases as a model system. 26 On a more applied front, successful computational manipulations of a number of challenging systems are presented. Bridging methodology and applications, Winther and co-workers use template-based design, experimentally and computationally assessing the effectiveness of different templates to redesign a thioredoxin from spinach, obtaining proteins with compact folded structures.…”
mentioning
confidence: 99%